2021
DOI: 10.3390/w13010095
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Annual and Seasonal River Runoff by Using Innovative Trend Analysis with Significant Test

Abstract: This study investigated the temporal patterns of annual and seasonal river runoff data at 13 hydrological stations in the Lake Issyk-Kul basin, Central Asia. The temporal trends were analyzed using the innovative trend analysis (ITA) method with significance testing. The ITA method results were compared with the Mann-Kendall (MK) trend test at a 95% confidence level. The comparison results revealed that the ITA method could effectively identify the trends detected by the MK trend test. Specifically, the MK tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The PBIAS values from verification using the modified model were better than that of the model before (Tables 4 and 5). The temperatures in Issyk-Kul's northern and southern catchments begin to rise in early April, snow begins to melt into stream flow, and the water levels in the catchments begin to rise rapidly [25], eventually leading to floods [97][98][99]. Our results showed that the participation of snowmelt from October to March was limited to the modified degree-day method, which increased from April to September.…”
Section: Model Performancementioning
confidence: 82%
See 1 more Smart Citation
“…The PBIAS values from verification using the modified model were better than that of the model before (Tables 4 and 5). The temperatures in Issyk-Kul's northern and southern catchments begin to rise in early April, snow begins to melt into stream flow, and the water levels in the catchments begin to rise rapidly [25], eventually leading to floods [97][98][99]. Our results showed that the participation of snowmelt from October to March was limited to the modified degree-day method, which increased from April to September.…”
Section: Model Performancementioning
confidence: 82%
“…The majority of glacial-snow-type rivers flow into Issyk-Kul [24]. River runoff's shifting properties have long been focuses of hydrological and water resource research [25]. Since Issyk-Kul's rivers affect its water level, it is important to focus on the sources of the rivers, especially the snowmelt.…”
Section: Introductionmentioning
confidence: 99%
“…GIS analysis method in the form of DEM analysis using Arc-View GIS software, which is supported by the Visual Basic programming language to add rain data. Software map-objects are combined to give a better view of the map [17]. The DEM analysis consists of topographic analysis of the location from art-view map data, which can then be followed by analysis of the slope of the location and analysis of the elevation model.…”
Section: Gis Analysis (Simodas)mentioning
confidence: 99%
“…Recently, trend analysis in hydrological series has received attention in the scientific community (Rosin et al, 2015;Pousa et al, 2019;Salehi et al, 2020;Alifujiang et al, 2021). This concern has been largely attributed to climate change, due to its impact on the hydrological cycle such as pandemics, low food productivity, reduced availability and quality of water, imbalance in ecosystems such as loss and fragmentation of habitats inducing the loss of biodiversity (Campbell et al, 2016;Das et al, 2018;Sharma et al, 2018;Moraci et al, 2020).…”
Section: Introductionmentioning
confidence: 99%